Impact Of Koinonia, Diakonia, and Marturia On Congregational Satisfaction at HKBP Cijantung Church - Maurit Simanjuntak; Timotius Tan; Timotius Bakti Sarono (Asosiasi Riset Ilmu Pendidkan Agama dan Filsafat Indonesia, 2024)
This study investigates the influence of Koinonia (fellowship), Diakonia (service), and Marturia (witness) on congregational satisfaction at HKBP Cijantung Church. Through a mixed-methods approach combining quantitative regression analysis and qualitative theological reflection, the research explores how these dimensions contribute to members' spiritual fulfilment and overall satisfaction within the church community. Statistical findings reveal a significant positive correlation between active engagement in fellowship activities, service-oriented initiatives, evangelistic efforts, and higher levels of congregational satisfaction. Theological insights underscore the biblical foundations of Koinonia, Diakonia, and Marturia, highlighting their role in shaping church identity and mission. Practical implications suggest enhancing these dimensions to foster community bonding, address social needs, and empower members in their faith journey. This research contributes to understanding the integral role of spiritual practices in church life and offers insights for church leaders seeking to cultivate vibrant, spiritually enriching communities.